2005
DOI: 10.4049/jimmunol.174.2.1020
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Lipoprotein Induces Resistance to Gram-Negative Sepsis in TLR4-Deficient Mice via Enhanced Bacterial Clearance

Abstract: TLRs are highly conserved pathogen recognition receptors. As a result, TLR4-deficient C3H/HeJ mice are highly susceptible to Gram-negative sepsis. We have previously demonstrated that tolerance induced by bacterial lipoprotein (BLP) protects wild-type mice against polymicrobial sepsis-induced lethality. In this study, we assessed whether pretreatment of C3H/HeJ mice with BLP could induce resistance to a subsequent Gram-negative Salmonella typhimurium infection. Pretreatment with BLP resulted in a significant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 40 publications
3
72
0
Order By: Relevance
“…Our in vivo work demonstrated that pretreatment with a nonlethal dose of BLP protects mice against not only a subsequent lethal BLP challenge, but also a subsequent lethal LPS challenge through a cross-tolerance to LPS (8). Unlike LPS tolerance, BLP tolerance-afforded protection against microbial sepsis was observed in both wild-type (WT) (8) and TLR4-deficient (9) mice. This is closely associated with BLP-induced reprogramming in phagocytes characterized by hypo-responsiveness in producing proinflammatory cytokines and simultaneously an enhanced antimicrobial activity (7)(8)(9).…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…Our in vivo work demonstrated that pretreatment with a nonlethal dose of BLP protects mice against not only a subsequent lethal BLP challenge, but also a subsequent lethal LPS challenge through a cross-tolerance to LPS (8). Unlike LPS tolerance, BLP tolerance-afforded protection against microbial sepsis was observed in both wild-type (WT) (8) and TLR4-deficient (9) mice. This is closely associated with BLP-induced reprogramming in phagocytes characterized by hypo-responsiveness in producing proinflammatory cytokines and simultaneously an enhanced antimicrobial activity (7)(8)(9).…”
mentioning
confidence: 93%
“…with 10 mg/kg BLP to induce BLP tolerance (BLP-tolerized), as described previously (8,9). Nontolerized mice received an equal volume (200 ml) of i.p.…”
Section: Mice and Lethal Blp Challenge In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…The adherence and phagocytic uptake of FITC-labeled, heat-killed E. coli (100°C for 1 h) were determined by flow cytometry as previously described by O'Brien et al (20). In brief, heat-killed E. coli were thawed and incubated in 0.1 M carbonate buffer (pH 9.5) in the presence 0.1% FITC (Sigma-Aldrich) for 60 min at 37°C.…”
Section: Measurement Of Peritoneal Neutrophil Activation Status and Pmentioning
confidence: 99%